SISTEM INFORMASI AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT BANTU DALAM PENILAIAN KINERJA MANAJEMEN PADA PT. PERKEBUNAN NUSANTARA III MEDAN - Lasma Melinda Siahaan; Antonius KAP Simbolon; Yohannes Cosmas Simbolon (JURNAL REGIONOMIC, 2019)
This research aims to analyze the accounting information responsibility system as a helping tool in the assessment of management performance in PT. Perkebunan Nusantara III Medan and to know wheter it has been useful for as a helping tool of management in the assessment of performance of cost center in PT. Perkebunan Nusantara III Medan. This research uses qualitative and secondary data. Qualitative data in question is the data in explanation form or description obtained from the quality of the object under study, while secondary data is a data obtained in the form that has been formed of Analysis of Work Plan Company Budget (RKAP) compare with the realization for 2013. This research is in the form of descriptive and deductive method. This method is done by collecting budget data and budget realization production which is then classified, interpreted, and analyzed to obtain an overview of the problems encountered in the object of research. While the deductive method is done by analyzing the data obtained and the object research by comparing the conceptual applicable general, so that can be drawn conclusions and given suggestions based on the research results. Based on the results of the study, the conclusion that Information Accounting Responsibility System as a helping tool of management in assessing the performance of the cost center in PT. Perkebunan Nusantara III Medan has shown its role formly and has been useful as a helping tool in the assessment of management performance cost